Expression of transforming growth factor beta in oral submucous fibrosis - Arpita Rai; Tanveer Ahmad; Shama Parveen; Saba Parveen; Md Imam Faizan; Sher Ali (Journal of Oral Biology and Craniofacial Research)
Background: Oral submucous fibrosis (OSMF) is a premalignant condition mainly caused by areca nut chewing and is characterized by progressive fibrosis of submucosal tissues and epithelial atrophy. Activation of transforming growth factor beta (TGF-β) signaling is considered main causative event for increased collagen production and fibrosis. In this study, molecular pathogenesis of OSMF was investigated based on the expression of the TGF-β genes in OSMF tissues compared to normal controls. Methods: A total of 33 OSMF and 10 normal tissues were collected from patients and their clinic-epidemiological data was recorded. The expression of TGF-β isoform genes- TGF β1, TGF β2, TGF β3 and its receptor TGF βR1, TGF βR2 was studied by real time polymerase chain reaction (PCR). Comparison of the expression of these genes among normal controls and OSMF patients was done. The PCR results were confirmed by histopathological and immunohistochemical staining. Results: The histological changes included atrophic epithelium, loss of rete ridges, presence of inflammatory cells and dense collagen bundles in connective tissue. PCR showed statistically significant upregulation of TGF-β isoforms in OSMF as compared to normal tissues. Of the three isoforms, maximum fold change was observed in TGF-β1. Similarly, both TGF-βR1 and TGF-βR2 were found to be elevated in OSMF tissues compared to normal. The semi-quantitative analysis by immunohistochemical staining revealed statistically significant difference between normal and OSMF tissues. Conclusion: TGF-β signaling plays a major role in the molecular pathogenesis of OSMF as shown by increased mRNA expression of all the three TGF-β isotypes and their receptors.